2023
DOI: 10.1039/d3bm00362k
|View full text |Cite
|
Sign up to set email alerts
|

Hydrophilic surface-modified 3D printed flexible scaffolds with high ceramic particle concentrations for immunopolarization-regulation and bone regeneration

Abstract: Bioceramic scaffolds used in bone tissue engineering suffer from a low concentration of ceramic particles (<50 wt%), because the high concentration of ceramic particles increases the brittleness of the composite....

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 56 publications
0
6
0
Order By: Relevance
“…Macrophages play a crucial role in osteo-immunomodulation because of their direct involvement in the initial inflammatory process of new bone formation [ 65 ]. The transition to the M2 phenotype has been demonstrated as crucial factor for the successful integration of implants and bone [ 66 ].…”
Section: Resultsmentioning
confidence: 99%
“…Macrophages play a crucial role in osteo-immunomodulation because of their direct involvement in the initial inflammatory process of new bone formation [ 65 ]. The transition to the M2 phenotype has been demonstrated as crucial factor for the successful integration of implants and bone [ 66 ].…”
Section: Resultsmentioning
confidence: 99%
“…In 3D-printed high-ceramic content composites of PCL and HAp, alkali surface modification was utilized to enhance the surface hydrophilicity of the PCL/hyaluronic acid scaffold, and regulate the immune responses. Results showed that the modification of scaffold by NaOH solution reduced foreign body reactions considerably and also promoted macrophage polarization towards the M2 phenotype and improved new bone formation [206]. It can be concluded that through using hydrophilic materials, and processes that alter surface groups and increase surface roughness, hydrophilicity can be improved and thus the fate of cells can be changed.…”
Section: Hydrophilicitymentioning
confidence: 98%
“…Surface chemistry plays a critical role in determining the interactions among BTE scaffolds and cells, proteins, and other biological components in the surrounding environment [206]. First, surface chemistry affects cell adhesion and migration.…”
Section: Surface Chemistry and Compositionmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast to traditional methods that focus on surface functional group engineering and biochemical molecule delivery, simulating the extracellular matrix microenvironment offers a more direct and effective strategy to regulate osteogenesis [ 14 , 15 ]. It has been discovered that altering the hydrophilicity of materials can modulate the behavior of bone marrow mesenchymal stem cells (BMSCs) and promote osteogenic differentiation [ 13 , 16 , 17 ]. Moreover, material stiffness can induce the expression of mechanosensitive proteins, the secretion of pro-angiogenic molecules, and accelerate bone healing [ 11 , 18 20 ].…”
Section: Introductionmentioning
confidence: 99%